A study on diversity and density of marine dinoflagellates in the Straits of Malacca - Alim, Azura (2001)
The objective of this study is to update and compare the species composition, distribution and abundance of dinoflagellate in the Straits of Malacca. The samples were collected during the JICA- MASDEC Straits of Malacca Expedition on board RIV K. K. Mersuji from November 23 to December 2, 1998 (northeast monsoon season) and March 25 to April 4, 1999 (pre southwest monsoon season) by using "Van Dorm" water sampler. A total of 78 dinoflagellate species from 21 genus, 13 families, and six orders under Division Pyrrophyta were observed and identified. During the northeast monsoon, Peridiniales was the dominant order accounting for 87.87% of the total dinoflagellate density, followed by Dinophysiales (5.49%), Prorocentrales (2.98%), Noctilucales (1.85%), Pyrocystales (1.45%) and Gymnodiniales (0.36%). Peridiniales also constitute of an important group during the pre southwest monsoon with an average 71.84% of the total dinoflagellate density, followed by Gymnodiniales (20.51%), Dinophysiales (4.80%), Pyrocystales (1.40%), Prorocentrales (0.89%) and Noctilucales (0.57%). In terms of numbers, the total density of dinoflagellates varied from 2.64 cells/l at Station 24 to 2.93 x 103 cells/l at Station 13 and 18.02 cells/l at Station 19 to 6.24 x 102 cells/1 at Station 14 during the northeast monsoon season and the pre southwest monsoon season respectively. The middle zone of the Malacca Straits showed the highest density of dinoflagellate compared to the northern and southern zone for both monsoon seasons. During the northeast monsoon, the density of dinoflagellate in the offshore stations was higher than in the inshore stations. In contrast, the inshore stations of the Straits showed the highest density of dinoflagellate compared to the offshore stations during the pre southwest monsoon. Ceratium furca was the most dominant species in the Straits of Malacca during the northeast monsoon (maximum cell density reached 2.87 x 103 cells/l at Station 13) and dominated dinoflagellate assemblages almost at all stations. Gymnodinium simplex, Protoperidinium ovum and Ceratium furca were the three most dominant species in the Straits of Malacca during the pre southwest monsoon. ANOVA showed a significant difference (F = 21.05, p < 0.05 and F = 11.66, p < 0.05) in species diversity and species evenness between the northeast monsoon and the pre southwest monsoon. However, there was no significant difference (F = 2.34, p > 0.05) in species richness between the northeast monsoon and the pre southwest monsoon.